Properties of suprathermal electrons associated with discrete auroral arcs. Issue 8 (30th April 2017) - Ogasawara, K.; Livadiotis, G.; Grubbs, G. A.; Jahn, J.‐M.; Michell, R.; Samara, M.; Sharber, J. R.; Winningham, J. D.
Abstract: We report on the properties of suprathermal electrons observed over three discrete auroral arcs from a sounding rocket. By applying shifted kappa distributions and analyzing kappa parameters (density, temperature, and kappa), we found three novel characteristics to provide clues to understand the auroral acceleration mechanisms and magnetosphere‐ionosphere coupling processes. First, the auroral potential drop was proportional to the inverse square of kappa, consistent with previous theoretical investigations by Dors and Kletzing (1999 ). The observed dependency was slightly stronger than their calculations, suggesting additional contributions from nonlinear plasma processes. Second, the polytropic relation showed nonadiabatic (near isothermal) state of the source electrons. This can provide a restriction on the pressure balance issues in the plasma sheet convection. Third, there was a clear difference in the polytropic and kappa indices for the first arc as opposed to the second and the third arcs, suggesting different source locations in the plasma sheet for the precipitating electrons that cause these nearby arcs. Key Points: The auroral potential drop was proportional to the inverse square of kappa, supporting previous theoretical investigations The obtained polytropic relation showed nonadiabatic state of the expected source electrons A clear difference in the polytropic index and the kappa indices between arcs suggested the different source populations